2021
DOI: 10.1016/j.optom.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a new intense pulsed light, thermaeye plus, in the treatment of dry eye disease due to meibomian gland dysfunction

Abstract: Purpose This study aims to estimate the efficacy and safety of a new intense pulsed light (IPL) Thermaeye Plus for dry eye disease (DED) secondary to meibomian gland dysfunction (MGD). Patients and methods This is a prospective, longitudinal study of patients with moderate to severe MGD. Treatment consisted of 4 consecutive IPL sessions, 12 flashes with the same energy 8 J/cm 2 on the periocular area at days 1, 14, 28, and 49. All patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…This non-comparative prospective case series has shown, as in previous studies, that IPL-based therapy can be an effective treatment for dry eye with MGD associated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In agreement with the mechanism of action of the IPL technology, a significant change was observed in the secretion of the meibomian glands, with more eyes showing clear or yellow secretions after therapy.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This non-comparative prospective case series has shown, as in previous studies, that IPL-based therapy can be an effective treatment for dry eye with MGD associated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In agreement with the mechanism of action of the IPL technology, a significant change was observed in the secretion of the meibomian glands, with more eyes showing clear or yellow secretions after therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Gupta et al [6] reported in a multicenter cohort study involving 100 patients with diagnosis of dry eye and MGD treated with IPL that there was a significant decrease in meibum viscosity scoring (mean: −1.1, range: −3 to 0) and a significant increase in oil flow score (mean: 0.9, range: −0.5 to 2.0). These changes in meibomian secretions are the responsible for the generation of a more consistent lipid layer [5,9,12] leading to increased values of BUT [5,8,9,[11][12][13][14][15]. In the current sample, no significant changes were detected in NIBUT.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations